Peningkatan Kinerja Guru melalui Supervisi Akademik pada SDN 3 Masbagik Timur Kecamatan Masbagik Semester Ganjil Tahun Pelajaran 2021/2022 - Mugni, Lalu (TSAQOFAH, 2021)
In this study the author tries to examine and explore supervision (principals) related to teacher performance, caused by: (1). There is a tendency to weaken teacher performance where based on the author's experience as a principal at SDN 3 Masbagik Timur, namely the existence of teachers who cannot carry out their roles and functions effectively, teachers who enter classes not on time, teaching teachers do not have teaching preparation, teachers do not have student absenteeism, (2) The implementation of supervision carried out by the principal has not been carried out as well as possible to the teacher. (3) The decline in teacher performance is one of the causes of the decline in student test scores at SDN 3 Masbagik Timur. The purpose of this school action research (PTS) is to find out the extent to which school principals develop in improving teacher performance through academic supervision. In this school action research (PTS), it was carried out in 2 cycles, from the results of the actions taken it was proven to be able to improve teacher performance by achieving ideal standards. From the average value of supervision results 63.33 in the first cycle, it can increase to 83.00. The results of this action research indicate that coaching through academic supervision can improve teacher performance at SDN 3 Masbagik Timur with completeness increasing from 33% in the first cycle and 100% in the second cycle.